How Important are Debt and Growth Expectations for Interest Rates? - Rafiq, Sohrab (IMF Working Papers; Working Paper ;, 2015)
This paper uses a dataset on private-sector risk aversion as well as expectations of long-run growth and debt to explain trends in implied forward rates on government bonds in the G-7 countries. The results show, consistent with the literature, that a one-percent rise in the long-run projected debt-to-GDP ratio causes an increase in bond yields of a relatively modest 1-to-6 basis points. Shocks to growth expectations and risk aversion have been comparatively more successful in explaining the behavior of long-term rates. The findings imply that growth policies rather than long-run projections of fiscal outcomes may be more important in helping influence long-term borrowing costs.